Semi-Flexible Material: A Solution for High-Performance Pavement Infrastructures. Issue 2 (February 2019) - Bonicelli, Alessandra; Preciado, Jaime; Rueda, Ana; Duarte, Alejandro
Abstract: Asphalt pavement technology has been widely adopted due its good mechanical performance, its excellent surface properties, the ease of construction and driving comfort. Nevertheless, asphalt pavements, commonly also known as "flexible pavements" have demonstrated to present high moisture susceptibility, low resistance to several chemical agents and poor long-term performance. Moreover, both high and low temperatures can produce different damages in flexible pavement such as rutting and cracking. On the other hand, rigid pavements have been losing popularity mainly due to the presence of transversal joints, required to consider the expansion of concrete slabs that produce a reduction of user-comfort and safety. In addition, Concrete pavement need longer construction procedure and a curing time before opening to traffic. Hence, a new technology has been developed in the last years in order to gather the essential properties that characterize rigid and flexible pavements. This technology, usually called semi-flexible pavements, or grouted macadam, consist in producing a highly open porous asphalt mix (voids around 25-30%) and filling the voids with selected cementitious grout. Thus, the ease and speed of construction of flexible pavement, joint with the optimal surface properties is combined with the concrete good mechanical behaviour, resistance to chemical agents and limited temperature susceptibility. The final product is a high performance pavement material, particularly indicated to high traffic volume roads, airports, ports, and industrial areas. However, the fact that this type of pavement is still innovative compared to rigid and flexible pavement has made that there is no standard procedure to produce this type of mixture. For this reason, the characteristics of the mixtures vary with authors and in the different real scale applications. In this manner, this paper aims at studying the most significant advances in the area of semi-flexible pavements, describing, comparing and statistically analysing the different investigation and practical experiences. Mix-design details, i.e., asphalt binder characteristics, aggregate properties and cementitious grout composition are deeply investigated, as well as mixing and compaction procedures, lab testing and real application performance of this innovative and promising pavement material.